PENGARUH SIFAT FISIKA MEDIA TERHADAP KEMAMPUAN BERAKAR DAN PEMBENTUKAN AKAR STEK PUCUK Shorea playlados DI PT. SARI BUMI KALIMANTAN TENGAH - Suryo Hardiwinoto; Adriana Adriana; Handojo Hadi Nurjanto; Widiyatno Widiyatno; Fransisca Dhina; Eko Priyo (Jurnal Pemuliaan Tanaman Hutan, 2010)
Seedling production of S. platyclados through vegetative propagation offers various advantages particularly mass production of good quality seedling in a certain time can be attained. Shoot cutting is affected by various factors including the physical properties of several media on rooting ability and early root development of S. platyclados shoot cuttings. Completely Randomized Design (CRD) was used with 6 replications. Three medium used were Dipterocarp wood sawdust, wood sawdust + rice husk (2/1), and rice husk charcoal. Result showed that wood sawdust bulk density was highest (0.36 kg/l) in compare to that of wood sawdust + rice husk (0.29 kg/l) and rice husk charcoal (0.17 kg/l). The bulk density has positively correlated (r = 0.97) with Water Holding Capacity (WHC) and negatively correlated with porosity (r = -0.99). Rooting ability of the shoot cutting in sawdust + rice husk (2/1) was highest (63%) in compare to that in wood sawdust (43%) and positively correlated with porosity (r=0.59). Early root development in the media did not show significant difference; however, the media of wood sawdust and wood sawdust + rice husk (2/1) tended to have a better early root development compare to rice husk charcoal.